Credible and actionable evidence : the foundations for rigorous and influential evaluations - Donaldson, Stewart I. (Stewart Ian); Christie, Christina A.; Mark, Melvin M. (Los Angeles : Sage, 2015)
Addressing one of the most important and contentious issues challenging applied research and evaluation practice toda?uwhat constitutes credible and actionable evidence?this volume offers a balanced and current context in which to analyze the long-debated quantitative-qualitative paradigms. In the Second Edition, the contributors, a veritable "who's who" in evaluation, discuss the diversity and changing nature of credible and actionable evidence; offer authoritative guidance about using credible and actionable evidence; explain how to use it to provide rigorous and influential evaluations; and include lessons from their own applied research and evaluation to suggest ways to address the key issues and challenges. Reflecting the latest developments in the field and covering both experimental and non-experimental methods, the new edition includes revised and updated chapters, summaries of strengths and weaknesses across varied approaches, and contains diverse definitions of evidence. Also included are two new chapters on assessing credibility and synthesizing evidence for policy makers. This is a valuable resource for students and others interested in how to best study and evaluate programs, policies, organizations, and other initiatives designed to improve aspects of the human condition and societal well-being.
Introduction -- Credible and actionable evidence : the role of randomized experiments -- Credible and actionable evidence : perspectives from a range of evaluation designs and methods -- Credible and actionable evidence : general perspectives.
Previous edition: What counts as credible evidence in applied research and evaluation practice? Los Angeles : Sage, 2009.
Includes bibliographical references and index.
Description based on MARC record for print version.
Keywords: elektronické knihy; electronic books; Research -- Evaluation; Research -- Social aspects; Social sciences -- Methodology; Evaluation research (Social action programs); Educational accountability